PENINGKATAN KETERAMPILAN MEMBUAT POLA DASAR ROK DENGAN POLA STANDAR MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD - ATIK ATIFAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to improve the skills of making basic skirt patterns with standard patterns through STAD type cooperative learning along with student activity in learning which is designed using second-cycle class action research. The subjects of this study were students of class XI of the Fashion Skills Program at MAN 2 Kudus for the 2017/2018 academic year, totaling 28 students. The research instrument consisted of lesson plans, observation sheets to collect data on student and teacher activities, and interview questionnaires to collect data on student responses to cooperative learning models conducted by teachers. While the paper and pencil test sheet instrument was used to collect data on students' skills in making skirt basic patterns in the form of a written test whose target was the student's ability to present images of the basic skirt pattern in a costume book. The data were analyzed quantitatively and qualitatively. Based on the analysis of the research data, it shows: 1) there is an increase in the skills of making basic skirt patterns with standard patterns in class X students of the fashion skills program at MAN 2 Kudus through cooperative learning type STAD with an increase in class average from 76 in the first cycle to 83.52 in the second cycle and the learning completeness in the first cycle was 53.57% and the second cycle increased to 100%. 2) there is an increase in student activity from 81.75% in the first cycle to 95.24% in the second cycle with a very good category. This can be seen in the activeness, cooperation and seriousness of students in participating in the STAD type of cooperative learning model. ABSTRAKPenelitian ini bertujuan adalah untuk meningkatkan keterampilan membuat pola dasar rok dengan pola standar melalui pembelajaran kooperatif tipe STAD berserta kaktivitas siswa dalam pembelajan yang didisain menggunakan penelitian tindakan kelas dua siklus. Subyek penelitian ini adalah siswa kelas XI Program Keterampilan tata busana MAN 2 kudus tahun pelajaran 2017/2018 berjumlah 28 siswa. Instrumen penelitian terdiri dari RPP, lembar observasi untuk mengambil data aktivitas siswa dan guru, lembar angket wawancara digunakan untuk mengambil data tanggapan siswa terhadap pembelajaran model kooperatif yang lakukan guru. Sedangkan instrumen lembar tes paper and pencil digunakan untuk mengambil data keterampilan siswa dalam membuat pola dasar rok berupa tes tertulis yang sasarannya adalah kemampuan siswa menyajikan gambar pola dasar rok di dalam buku kostum, Data dianalisis secara kuantitatif dan kualitatif. Berdasarkan analisis data penelitian menunjukkan: 1) terdapat peningkatan keterampilan membuat pola dasar rok dengan pola stándar pada siswa kelas X program keterampilan tata busana MAN 2 Kudus melalui pembelajaran kooperatif tipe STAD dengan peningkatan rata-rata kelas dari 76 pada siklus I menjadi 83,52 pada siklus II dan ketuntasan belajar pada siklus I sebesar 53,57% dan siklus II meningkat menjadi 100%. 2) terdapat peningkatan aktivitas siswa dari 81,75% pada siklus I meningkat menjadi 95,24% pada siklus II dengan kategori sangat baik. Hal tersebut terlihat pada keaktifan, kerjasama dan kesungguhan siswa dalam mengikuti pembelajaran model kooperatif tipe STAD.